Reimagining madrasah education management: Critical and sustainable strategies for advancing the SDGs - Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (Tadibia Islamika: Journal of Holistic Islamic Education, 2025)
The consistently low student enrollment at Madrasah Aliyah Nurul Rahmat, averaging around 30 students per cohort, presents a significant challenge to the institution’s growth and visibility. As a religious educational institution, the madrasah is often expected to affiliate with larger national or urban schools to improve accessibility and recognition. This study aims to examine the transformation of education management at Madrasah Aliyah Nurul Rahmat from 2018 to 2024, focusing on advancing Sustainable Development Goals (SDGs) through critical and sustained educational efforts. Employing a qualitative, exploratory approach, data were collected through silent observation and in-depth interviews with the madrasah’s head, teachers, and students. The findings indicate that despite various challenges, visionary leadership grounded in religious principles has successfully fostered a strong religious ethos, an inclusive learning environment, and increased student productivity. Students’ academic performance has shown continuous improvement across multiple subjects, supported by teachers’ dedication to professional growth and the cultivation of student leadership skills. Additionally, graduates have achieved notable success at both local and national levels, reflecting the effectiveness of the implemented educational strategies. These results highlight the critical role of effective leadership and innovative management in transforming educational institutions to meet broader developmental goals, suggesting that similar approaches could be beneficial in comparable contexts.